2014
DOI: 10.1007/s10753-014-9897-y
|View full text |Cite
|
Sign up to set email alerts
|

CRP Gene (1059G>C) Polymorphism and Its Plasma Levels in Ischemic Stroke and Hemorrhagic Stroke in a South Indian Population

Abstract: In the present study, we evaluated the association of 1059G>C polymorphism in C-reactive protein (CRP) gene with the risk of ischemic and hemorrhagic strokes. We did not find a significant association of this polymorphism with stroke. However, 2 % of mutants were observed in hemorrhagic stroke patients with a 0.01 frequency for the C allele. We also estimated the high-sensitivity C-reactive protein (hsCRP) levels in hemorrhagic stroke and compared the levels with our already published data on ischemic stroke. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…After the onset of acute ischemic stroke, the inflammatory activities could further promote the brain damage, and C-reactive protein is a common inflammatory factor which has been reported that its level is connected with the severity of neurological deficit and disability after stroke (Das, Roy, Kaul, Jyothy, & Munshi, 2004). In addition, fibrinogen, which was also detected in this study, is regarded as a key regulator of inflammation in disease.…”
Section: Discussionsupporting
confidence: 56%
“…After the onset of acute ischemic stroke, the inflammatory activities could further promote the brain damage, and C-reactive protein is a common inflammatory factor which has been reported that its level is connected with the severity of neurological deficit and disability after stroke (Das, Roy, Kaul, Jyothy, & Munshi, 2004). In addition, fibrinogen, which was also detected in this study, is regarded as a key regulator of inflammation in disease.…”
Section: Discussionsupporting
confidence: 56%
“…It is a well-known fact that both ischemic and hemorrhagic stroke can cause inflammatory responses due to brain tissue injury that occurs in both types of stroke [14] [28]. Recently published studies found that CRP level is elevated in patients with ischemic stroke [29] and haemorrhagic stroke [30,31], which shows that inflammatory response occurs in these 2 types of stroke, which was also found in the current study. This might be explained by the general rise in CRP in the observed group of patients with risk factors for stroke: heart disease [32], atrial fibrillation, and heart failure [33].…”
Section: Discussionsupporting
confidence: 87%
“…A Chinese case-control study including 548 patients with acute IS and 993 age-matched control subjects indicated that rs3093059 was statistically significantly associated with IS [14]. However, controversial views still remain [18,[35][36][37] and that was in accordance with our results.…”
Section: Single Polymorphism Analysissupporting
confidence: 90%